The heart-led leader : how living and leading from the heart will change your organization and your life - Spaulding, Tommy (Recorded Books, 2015)
Authentic leaders, Spaulding says, live and lead from the heart. The values and principles that guide our lives and shape our ability to lead others is far more important than our title, or our ability to crunch numbers, or the impressive degrees we display on our walls. To effect true transformational change, heart-led leaders draw on the qualities of humility, vulnerability, transparency, empathy and love. Illustrated with stories from his own life, and from some of the exceptional leaders he has met and worked with over the years, Spaulding unpacks what those qualities mean, talks about the 18-inch journey from the head to the heart - from our intellect to our emotions - and shows us how to incorporate them into our careers, into how we manage and lead others, and into how we live our lives. It is a vision of leadership that has the power to transform everything we do, and the lives of everyone we touch.